Uji Efek Immunomodulator Dari Ekstrak Daun Manggis (Garcinia mangostana L.) Dengan Metode Carbon Clearence dan Menghitung Jumlah Sel Leukosit Pada Mencit Putih Jantan - Yufri Aldi; Sri Oktavia; Sirda Yenni (Jurnal Farmasi Higea, 2016)
The research of immunomodulatory effect  from the  mangosteen (Garcinia mangostana) leaves ethanol extract with a carbon clearance method and the counting of leukocytes cell amount in male white mice. Has been done the ethanol extract of mangosteen (Garcinia mangostana) leaves is given to every mouse during six days with a 100 mg/kg BW, 300 mg/kg BW, and 900 mg/kg BW dose. In the seventh day, it has been decided a phagocyte index and the percentage amount of neutrophils, eusinofil, basophile, monocytes and lymphocytes. The result of the research is showing a given ethanol extract of mangosteen (Garcinia mangostana) leaves at the 100 mg/kg BW, 300 mg/kg BW, and 900 mg/kg BW dose, it can increase a phagocytes index that is >1and  increase the amount of leukocytes cell that the extract has a characteristic of immunostimulatory.